Greetings from Trinidad, B.W.I. - (:unkn) unknown (H.O. Thomas, [Trinidad and Tobago], 2011)
Description printed on the back of the postcard: "Pezance Point, one of the many scenic beauties enjoyed by visitors on their way to Toco on the North East coast." Postcard number 29237.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Scenic overlooks--Trinidad and Tobago; Coasts--Trinidad and Tobago